Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0123414
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Increased Visceral Adiposity Index in Prehypertension

Abstract: BackgroundThe prevalence of prehypertension has increased in China, and prehypertension frequently progress to hypertension over a short time period; both have become public health problems. Therefore, this study was conducted to determine the relationship between the Visceral Adiposity Index (VAI) and blood pressure (BP) in China.MethodsA cross-sectional epidemiological survey was conducted in China using a stratified random cluster sampling method. Sex-specific VAI quartile cut-off points were used as follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 39 publications
6
36
0
1
Order By: Relevance
“…Recently, VAI, not total or subcutaneous adiposity, has been proven to be a good predictor of prehypertension and hypertension [38,39]. However, additional studies are needed to elucidate the mechanisms underlying this association.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, VAI, not total or subcutaneous adiposity, has been proven to be a good predictor of prehypertension and hypertension [38,39]. However, additional studies are needed to elucidate the mechanisms underlying this association.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Amato et al [16] suggested visceral adiposity index (VAI) to predict cardiometabolic risk in adult women and men. Furthermore, Ding et al [17] demonstrated a significant relationship between BP levels and VAI, in a Chinese population. However, it is still needed further investigation that allows clarifying the advantages of this tool in the screening of hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…This index combined both anthropometric and metabolic variables to evaluate body fatness, and was used as a marker of both visceral fat dysfunction and an individual's subsequent cardiometabolic risk. A number of studies were conducted to investigate the association of VAI with several conditions, and VAI has been suggested as a useful and convincing surrogate marker of metabolic syndrome [14,15] , arterial stiffness [16] , hypertension and prehypertension [17] , type 2 diabetes [18,19] , and cardiovascular events and mortality [20] . To date, sparse data about the relationship between VAI and pre-diabetes among Chinese population have reported; therefore, we conducted this study to investigate the associations of VAI with both pre-diabetes and diabetes, and to compare the predictive ability for dysglycemia between VAI and other obesity indices including BMI, WC, WHR, and WHtR.…”
Section: Introductionmentioning
confidence: 99%